Isolation Of Lactobacillus Brevis C23 For Production Of Bacteriocin-Like Inhibitory Substance Against Food Borne Pathogen, Listeria Monocytogenes - Sreedharan, Dharni Kuhan (2021)
Bacteriocins have drawn interest due to the ability to inhibit pathogen and safe. This study aims to isolate lactic acid bacteria (LAB) from various food sources to obtain a potent strain against L. monocytogenes for a potential use in food preservation and packaging. Broth microdilution method was utilized to measure the effectiveness of isolated strains against L. monocytogenes.